Usage and adherence of antidementia drugs in a memory clinic cohort in Chongqing, Southwest China: Neuropsychiatry and behavioral neurology/Dementia. (7th December 2020) - Yu, Xingyan; Yu, Weihua; Yang, Wenkai; Lü, Yang
Abstract: Background: To investigate the use and adherence of anti‐dementia drugs in elderly patients with dementia from the Memory Clinic of The First Affiliated Hospital of Chongqing Medical University. Method: Patients were recruited from the Memory Clinic of The First Affiliated Hospital of Chongqing Medical University between December 2010 and December 2018. The medical chart was reviewed, including diagnosis, dosage of antidementia medicine, neuropsychological testing scores, and the further questionnaires were conducted via face‐to‐face or telephone, included duration of treatment, types of anti‐dementia drugs, and reasons for treatment discontinuation. Result: The data from 422 patients were analyzed retrospectively for this study. 315 were diagnosed with AD, 67 with MCI, and 40 with other types of dementia. From the 422 patients, 26.8% were treated with original donepezil, 11.6% with generic donepezil, 24.6% with memantine, 13.3% with huperzine A, and 23.7% with a combination of drugs. However, 73% of patients discontinued treatment within one year of initiation. Patients with less than nine years of education were more likely to discontinue treatment than patients with more than nine years of education. Patients with elevated PSMS scores had a high risk of discontinuation. Patients had a higher risk of discontinuation when they had received treatment for less than 36 months. Conclusion: Overall treatment compliance is relatively poor in memory clinic in Chongqing. Our study demonstrates that high education, combined medication may lead to better treatment adherence in dementia care. However, poorer PSMS is a significant risk factor for treatment discontinuation.